Pengaruh Penggunaan Bottom Ash Sebagai Pengganti Semen Dengan Perendaman NaCl Terhadap Sifat Mekanik Beton - Stefanny; Jonie Tanijaya; Suryanti Rapang Tonapa (Paulus Civil Engineering Journal, 2020)
Based on Government Regulation (PP) No. 101 of 2014 bottom ash is categorized as hazardous and toxic waste (B3). Therefore, the author utilizes bottom ash waste as an alternative substitution of concrete mixture material to reduce environmental pollution. Most of the earth's surface is marine territory, the most dominant salt element contained in seawater is NaCl which is known to be aggressive towards concrete. This study was conducted to find out the influence of bottom ash percentage on concrete mixture. From the results of the study obtained a strong value press 28 days in a row of 26,031 MPa, 25,182 MPa, and 23,201 MPa. Based on this research, it can be known that the mixture of concrete with bottom ash substitution causes concrete to decrease strength as the percentage of bottom ash substitution increases.